2016
DOI: 10.1164/rccm.201508-1655oc
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Tachypnea of Infancy. Usual and Aberrant

Abstract: RATIONALE: Persistent tachypnea of infancy (PTI) is a specific clinical entity of undefined etiology comprising the two diseases neuroendocrine cell hyperplasia of infancy (NEHI) and pulmonary interstitial glycogenosis. The outcome of typical NEHI is favorable. The outcome may be different for patients without a typical NEHI presentation, and thus a lung biopsy to differentiate the diseases is indicated. OBJECTIVES: To determine whether infants with the characteristic clinical presentation and computed tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 24 publications
6
68
0
Order By: Relevance
“…Cases of chronic tachypnoea of infancy (usual or aberrant) had no biopsy and were defined as described previously;16 cases were only labelled ‘Neuroendocrine cell hyperplasia of infancy’ if there was proof by biopsy and concordant clinical symptoms. Details on the classification system and definitions used are given in the supplement of Griese et al 12…”
Section: Resultsmentioning
confidence: 99%
“…Cases of chronic tachypnoea of infancy (usual or aberrant) had no biopsy and were defined as described previously;16 cases were only labelled ‘Neuroendocrine cell hyperplasia of infancy’ if there was proof by biopsy and concordant clinical symptoms. Details on the classification system and definitions used are given in the supplement of Griese et al 12…”
Section: Resultsmentioning
confidence: 99%
“…The European guidelines do not make recommendations on the type of surgical approach [20]. The benefit of surgical biopsy remains controversial, particularly in well patients and in those with persistent tachypnoea of infancy [25]. However histological diagnosis may guide treatment decisions, especially withdrawal of care [24].…”
Section: Discussionmentioning
confidence: 99%
“…RAUCH et al [20] collected a cohort of 89 such infants, after the exclusion of other conditions, including surfactant dysfunction disorders, immune deficiencies, cystic fibrosis, primary ciliary dyskinesia and cardiac disease. This condition is called persistent tachypnoea of infancy (PTI).…”
Section: Dpld Group A3: Infant Conditions Of Undefined Aetiologymentioning
confidence: 99%
“…They found that the age of onset of symptoms (3.5 (range 0-20) months), the initial symptoms (tachypnoea 100%, crackles 86%, retractions 82%, failure to thrive 66% and hypoxaemia 88%) were not different between usual and aberrant PTI. After an average follow-up until 4.2 (range 0.7-10.5) years, 50% of the infants were healthy, 46% were still sick, but had improved, and only 4% were in the same clinical condition [20]. It is of great importance to know and recognise this condition, in order to avoid overtreatment or to miss treatments necessary for similar conditions.…”
Section: Dpld Group A3: Infant Conditions Of Undefined Aetiologymentioning
confidence: 99%